Learners’ conceptualisation of the sine function during an introductory activity using sketchpad at grade 10 level - Villiers, Michael de; Jugmohan, Janeeshla (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2012)
This paper outlines a study that investigated and analysed learners’ conceptualisation of the sine function during an introductory activity, using Sketchpad at Grade 10 level. In the analysis of the learners’ understanding of the sine function, correct intuitions as well as misconceptions in their mathematics were identified. The use of Sketchpad to introduce the sine function proved to be a reasonably successful and meaningful activity in developing understanding of some significant aspects of the sine function.